Narcissistic Traits and Executive Functions - Nenadić, Igor (Frontiers in Psychology, 2021)
Several personality disorders have been associated with cognitive impairment, including executive functions like working memory. Yet, it is unclear whether subclinical expression in non-clinical persons is associated with cognitive functioning. Recent studies indicate that non-clinical subjects might, in fact, perform better with increasing moderate to mild expressions of narcissistic features. We tested working memory performance in a cohort of n=70 psychiatrically and neurologically healthy subjects using Wechsler Adult Intelligence Scale (WAIS/WIE) subtests arithmetic, digit span, and letter-number-sequencing; and assessed narcissistic features using three different inventories: the widely used narcissistic personality inventory (NPI), as well as two clinically used measures of narcissistic traits and states, resp., derived from schema-focused therapy, i.e. the YSQ (Young schema questionnaire) entitlement subscale and the SMI (schema mode inventory) self-aggrandizer subscale. In accordance with our hypothesis, we found nominally significant positive correlations of WIE arithmetic performance with NPI total score (p=0.043) and SMI self-aggrandizer scale (p=0.027), but not the other two WIE subtests, and findings did not survive false discovery rate (FDR) adjustment for multiple comparisons. While our findings corroborate and extend recent findings on cognitive performance in subclinical narcissism, they fail to demonstrate this association across multiple working memory tests, indicating the need for additional study , including complementary executive functions in larger cohorts and ranges of phenotype expression.